Dengue Awareness in Latin American Populations: A Questionnaire Study - Sarti, Elsa (Infect Dis Ther, 2015)
INTRODUCTION: Dengue is an escalating public health concern in Latin American Countries with a dramatic increase of cases reported during the past decade. The objectives of this study were to identify and provide insights into current management and attitudes toward dengue and to understand attitudes to vaccination and current behaviors to prevent dengue in Mexico and Colombia. METHODS: This was a community-based, cross-sectional, descriptive study conducted in urban and rural areas in endemic and non-endemic regions. The interviews were conducted face-to-face using a structured questionnaire containing 58 questions. A quota sampling approach was used to obtain a nationally representative sample of the adult population. All data were weighted to correct for differences between the samples surveyed in each country relative to their general population. RESULTS: A total of 1978 participants completed the survey. Two percent and 10% of participants in Mexico and Colombia, respectively, had experienced dengue fever, with just under one-third of adults and almost two-thirds of their children hospitalized as a result of the illness. Awareness of dengue was similar in Colombia (76%) and Mexico (68%), with awareness higher in endemic regions than in non-endemic regions. Colombia had a higher proportion of participants (84%) who considered dengue to be a common disease in their country, compared with Mexico (56%). In Mexico and Colombia, 55% and 54% in endemic areas, and 28% and 46% in non-endemic areas believed that everyone was at risk of contracting dengue. In both countries, the most common action undertaken by participants to prevent dengue infection was removal of standing water. At least 70% of participants believe their government could do more to prevent dengue in their country. CONCLUSIONS: Dengue was identified as a severe and common disease in Mexico and Colombia. Most participants recognized the need to reduce the risk of dengue infection by removal of standing water. Awareness was similar in Colombia and Mexico. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40121-015-0068-8) contains supplementary material, which is available to authorized users.